Teaching science subjects in Arabic: Arab university scientists’ perspectives - Alhamami, Munassir (Language learning in higher education (Berlin, Germany), 2015)
This study investigates Arab university scientists’ views of the status of English and Arabic in the 21st century, and their attitudes towards using English and Arabic as media of instruction in science faculties in the Arab world. Twenty-seven science instructors at a Saudi University coming from different backgrounds responded to a written survey, and the data were analyzed quantitatively and qualitatively. The findings reveal that the majority of the science instructors preferred to use the students’ mother tongue (Arabic) to teach science, even though the current policy is to use English as the medium of instruction. The results indicate that, from the perspective of Arab scientists, English as medium of instruction in Saudi universities presents academic and social challenges in science education at university undergraduate level.